Chromosome mapping of retrotransposable elements Rex1 and Rex3 in Leporinus Spix, 1829 species (Characiformes: Anostomidae) and its relationships among heterochromatic segments and W sex chromosome - Splendore de Borba, Rafael [UNESP]; Lourenço da Silva, Edson; Parise-Maltempi, Patrícia Pasquali [UNESP] (Taylor & Francis Group content, 2013)
The family Anostomidae is an interesting model for studies of repetitive elements, mainly because of the presence of high numbers of heterochromatic segments related to a peculiar system of female heterogamety, which is restricted to a few species of Leporinus genus. Thus, cytogenetic mapping of the retrotransposable elements Rex1, Rex3, and Rex6 was performed in six Leporinus species, to elucidate the genomic organization of this genus. The sequencing of the Rex1 and Rex3 elements detected different base pair compositions in these elements among species, whereas the Rex6 element was not identified in the genomes of these species. FISH analysis using Rex1 detected different distribution patterns, L. elongatus, L. macrocephalus, and L. obtusidens had clusters in the terminal regions, whereas the signals were dispersed throughout all of the chromosomes with some signals in the terminal position in other species. The Rex3 signals were found mainly in the terminal positions in all the chromosomes of all species. The W chromosomes of L. elongatus, L. macrocephalus, and L. obtusidens contained the Rex1 and Rex3 signal in an interstitial position. These results suggest the emergence of different activity levels for these elements during the evolution of the species analyzed. Despite the conserved karyotype macrostructure species Leporinus often discussed, our results show some variation in hybridization patterns, particularly between the species with specific patterns in their sex chromosomes and species without this differentiated system.
Keywords: Fish; Mobile dna; Repetitive sequences; Sex chromosome; Transposable elements